A Phase II Study of Flavopiridol in Patients With Previously Untreated Advanced Soft Tissue Sarcoma - Morris, Don G. (Hindawi Publishing Corporation, 2006)
Purpose. Flavopiridol is a potent cyclin-dependent kinase (CDK) inhibitor that has preclinical activity in many tumours. This synthetic flavonoid was tested in a phase II nonrandomized, nonblinded multicentre clinical trial to determine its activity and toxicity in patients with previously untreated metastatic or locally advanced soft tissue sarcoma. Methods. A total of 18 patients with histologically confirmed nonoperable soft tissue was treated with flavopiridol administered at a dose of 50 mg/m (2) IV over 1 hour daily ×3 days every 3 weeks. Results. Eighteen patients were accrued to the study over a period of 6 months. No objective responses were noted in the seventeen evaluable patients. Eight patients (47%) exhibited stable disease after 2 cycles (median duration of 4.3 months (range 1.4–6.9 months). Kaplan-Meier estimates for 3- and 6-month progression-free survivial rates were 44 percent and 22 percent, respectively. The only grade 3 toxicities were diarrhea (N = 2), nausea (N = 2), gastritis (N = 1), and fatigue (N = 1). Ninety-four percent of patients received ≥ 90% of the planned dose intensity, during 55 treatment cycles. Conclusions. Flavopiridol was well tolerated at the dose and schedule used in this study, however, no objective treatment responses were seen and thus our results do not support further exploration of flavopiridol as a monotherapy at this dose and schedule in soft tissue sarcomas.